Do skin suits affect the average skating speed? - Kuper, G. H.; Sterken, E. (Sports Technology, 2008)
We analyze the effectiveness of speed skating suits to allow for increases in average skating speed. We used the full set of speed skating results of the 2002 Olympic Winter Games of Salt Lake City and modeled the average skating speed of both male and female speed skaters at distances from 500 to 10 000 m. Speed correlates with the physical characteristics of the skaters, past performance, and technical equipment, like speed skating suits that reduce drag. Nike's Swift Skin suit seems to outperform other suits in terms of results, but once corrected for selection bias, we found that none of the suits outperform the others.